Behavior based definition of dependability for autonomous mobile systems - Rüdiger, Jan; Wagner, Achim; Badreddin, Essameddin (Control Conference (ECC), 2007 European, 2007)
In this paper a formal definition for dependability of autonomous mobile systems is proposed. The presented concept is based on the framework of Willems. The definition for dependability aims at providing the system designer/architect with a method for analysing the dependability of autonomous mobile systems.
Gesehen am 18.06.2019